Pendidikan Entrepreneurship Perguruan Tinggi Keagamaan Islam Swasta (Studi Kasus Di STIT Makhdum Ibrahim Tuban) - Siti Nurjanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, entrepreneurship education is a necessity needed to answer the challenges in the world of work. However, to implement entrepreneurship education, higher education requires planned strategic steps in order to achieve entrepreneurship education goals. This research was conducted to obtain an overview of the planning, implementation and evaluation of Entrepreneurship Education in Private Islamic Religious Institutions at STIT Makhdum Ibrahim Tuban, supporting factors for success and obstacles faced in the realization of Entrepreneurship Education and solutions made by STIT Makhdum Ibrahim Tuban. This study uses descriptive qualitative research methods, namely conducting research oriented to natural phenomena or symptoms. while the data collection techniques used in this study were observation, interviews and documentation. And to check the validity of the data the researcher uses source triangulation, which is checking the degree of trustworthiness of information obtained through different times. The results of the study show that 1) At the planning stage of the entrepreneurship education program, it requires many parties involved in the preparation of the program, including the BPP, the leaders of Higher Education, lecturers, students and stakeholders. In implementing entrepreneurship education through the integration of entrepreneurship values into courses and through extracurricular activities. As for measuring the success of the program, it is integrated into the course and checklist list and development table. The results of the next research are supporting factors, including the vision of structured STIT Makhdum Ibrahim Tuban, Study Program integrates entrepreneurship education into the curriculum and Supports the implementation of Ibrahim Tuban's STIT Makhdum Vision by the entire academic community. And the results of subsequent research are constraints and solutions, including the Guidelines for establishing a Vision, Mission of each Study Program not yet available. The efforts or solutions to overcome the obstacles to entrepreneurship education at STIT Makhdum Ibrahim Tuban are carried out by developing guidelines for establishing Vision, Mission and forming commissions. Raker Commission Keywords: Entrepreneurship Education, Private Islamic Religious College